Política pública de financiamento do ensino superior em tempo de crise: estratégias de gestão em uma instituição particular. - Guterres, Everton Luis de Lima (2019)
This dissertation demonstrates the student financing fund (FIES) and its impact on a private institution in the interior of Rio Grande do Sul, and it should be remembered that FIES is a public financing policy focused on private higher education. The lack or reduction of this policy implies directly in the institutional rates, among them, the number of students and the financial flow of the institution. As a temporal cut for the research, the period from 2012 to 2018 was used. The choice is justified by the large number of contracts of that time, as well as the changes that occurred during this period, allied to the political and economic crisis experienced in that period. These aspects reaffirmed the importance of this research for notes on the impact that policy exerted within the institution of private higher education, as will be demonstrated in what educational managers think and what strategies they used, both during this period of great growth of the program, and its decline. With the analysis of the results obtained in the research, an intervention plan was designed to optimize the decision-making processes and also to avoid the evasion of the students during the period they will spend in the institution. The results found in this research pointed to the decline in the number of students and, consequently, in financing contracts, challenging managers to develop strategies to guarantee results that maintain the Institution's sustainability.